The unlucky launch - Neal, Rie; Shipman, Talitha (New York : Aladdin, 2022)
When Astrid and her fellow Shooting Stars build a rocket, Astrid is hoping to impress guest helper, Leah, to score a tour of Space-E headquarters, but when she and her classmates discover Leah does not know much about rockets, Astrid is unsure if she should speak up.
Includes excerpt from next in series, Hydroponic Hijinks.
Ages 6 to 9.
Keywords: Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Cooperativeness -- Juvenile fiction; Rockets (Aeronautics) -- Juvenile fiction